Policy discourses on climate change, mobility, and conflict and fragility: Jordan - Schapendonk, Frans; Scartozzi, Cesare Marco; Passaro, Alessia; Laderach, Peter; Pacillo, Grazia (2024)
This policy brief assesses the current state of play of Jordan’s policy landscape with regards to the intersection of climate change, human mobility, and conflict and fragility. Through the deployment of an ex-ante content analysis, relevant national and sectoral policy and strategy documents are assessed to identify, firstly, whether the climate-mobility-fragility nexus features as a strategic consideration across various sectoral policy agendas within Jordan, and secondly, detect dominant narrative framings of the nexus within the policy discourse. We find that forced migration relating to conflict is the most frequently discussed form of mobility within the Jordanian policy landscape, and that the most common thematic factors associated with mobility include economic, security, and climate and environmental factors. Such issues tend to be framed as consequences - rather than drivers - of mobility. Finally, we identify that the extent to which Jordan has managed to successfully integrate refugee populations into strategic planning frameworks for climate adaptation and mitigation remains limited.